Role of Splenic Artery Embolization in Gastric Variceal Hemorrhage due to Sinistral Portal Hypertension - Sebastian, Bibin; Singhal, Soumil; Madhurkar, Rohit; Alex, Arun; Uthappa, M. C. (Journal of Clinical Interventional Radiology ISVIR, 2019)
Sinistral or left-sided portal hypertension is a localized form of portal hypertension usually due to isolated obstruction of splenic vein. Most commonly, it is secondary to pancreatitis. Rarely this can present as life-threatening gastric variceal bleeding. In such patients, splenectomy is traditionally considered as the treatment of choice to relieve venous hypertension. Unfortunately, a surgical operation may not be safe in most of the patients because of the unfavorable operative field. Splenic artery embolization (SAE) is an effective method, theoretically akin to splenectomy, blocking the direct arterial inflow to the spleen and thereby reducing the outflow venous pressure. The authors demonstrate a case of a 58-year-old man who presented with severe gastric variceal hemorrhage due to sinistral portal hypertension (SPH) secondary to an episode of pancreatitis, which he had 1 month back. He was successfully managed by SAE and remains symptom-free. The authors bring to the fore the potential curability of gastric variceal hemorrhage secondary to SPH using SAE, which is a safe and effective interventional radiologic procedure.
Keywords: sinistral portal hypertension; splenic artery embolization; fundal gastric varices; splenic vein thrombosis